Conhecimentos tradicionais: um estudo sobre as histórias e narrativas orais das práticas extrativistas da coleta da castanha na comunidade Santo Isidoro/ Tefé-AM - Zurra, Raizinara de Oliveira (2019)
Traditional knowledge in the Amazon has historically been one of the main elements of the way of life of rural communities in the region. Thus, the extraction and cultivation of different species, such as Brazil nuts, management, purpose and form of use contribute to conservation in these environments. Traditional communities usually maintain a cultural diversity to be preserved, so the transmission of traditional knowledge is passed from generation to generation, valuing all the traditional knowledge of these populations. This paper aims to analyze the traditional knowledge from the oral histories and narratives about the extractive practices of the nut gathering in the Santo Isidoro community in Tefé-AM. The analysis had as its guiding axis the narratives told by the old residents of the community in line with the traditional knowledge evidenced through the historical process about the extraction of Brazil nuts that occurred from 1960 until the years of 1980. This is a qualitative study, supported by the narrative bias as a research tool analyzed through interviews with the objective of understanding the community history regarding the collection of nuts and how the process of changes in the fruits occurred. extractive practices and what the impacts have been after declining over the current extraction of nuts in the community. The data analysis showed that the narrative contents present a temporality about the chestnut extractivism narrated by the research subjects inserted in the Santo Isidoro community.